Business - Pride, William M. (Houghton Mifflin Co., 2008)
The Ninth Edition of this bestselling introductory text features a completely up-to-date, comprehensive survey of the functional areas of business: management, marketing, accounting, finance, and information technology. Core topics highlighted within these areas include ethics and social responsibility, forms of business ownership, small business concerns, and international issues. New coverage in the Ninth Edition more closely examines economics, the role of teams, customer relationship management, and globalization. In addition to updating and revitalizing the content, the authors have redesigned the entire textbook program to highlight its strengths as the most accessible and student friendly program on the market. The "Your Guide to an A" passkey ensures student success and mastery through premium online study content, including ACE Plus practice tests, flashcards, MP3 audio chapter summaries and quizzes, interactive games, and Career Snapshots